Are Athletes Playing for Osteoarthritis? A Systematic Review - Butt, Muhammad Salman; Saleem, Javeria; Salman, Saifa; Irfan, Izza; Rashid, Mehnaz; Bukhari, Gul Mehar Javaid; Faryal, Joham (Journal of University College of Medicine and Dentistry, 2022)
Abstract Background An athlete suffers from many injuries in his sports career which may be due to some trauma or maybe atraumatic. Athletes involved in the sports of long-running remains worried about knee osteoarthritis (O.A) and a question always remain in a debate that physical activity is a risk of O.A and the athletes are running for osteoarthritis. This systematic review was conducted to synthesize the evidence on the quantitative association between participation in specific sports and the occurrence of Knee OA. This systematic review will also analyze the effect of sports injuries on knee OA. Methods Three electronic databases including PubMed, Scopus, and Springer link are selected for gathering the information and the articles for this study. This systematic review is based on the randomized control trials (RCTs), cohort and case-control studies published in the last 20 years (2000-2022) evaluating the symptomatic or asymptomatic tibiofemoral knee osteoarthritis change. The quality for study methodology was evaluated by using the Cochrane Effective Practice and Organization of Care Risk of Bias Tool and PRISMA checklist as a reference. Review manager, 5.4.1 Cochrane Collaboration was used for analyzing the risk for bias of individual studies. Results A total of 508 articles were searched and nine articles were selected to synthesized the results of this systematic review. Total nine articles are selected to conclude the results based on the inclusion criteria. Graph 1 is showing the study design and the number of included and excluded articles. The results are synthesized on the following levels using the PICOS model, i) comparison of running sports and incidence of knee osteoarthritis, ii) comparison of soccer, gender, and incidence of knee osteoarthritis, iii) comparison of anterior cruciate injury, the effect of treatment and incidence of knee osteoarthritis, and iv) comparison of training and prevention of knee osteoarthritis incidence. Conclusion Sports with more jumping, twisting, and knee injuries contribute to the prevalence of knee osteoarthritis. Knee osteoarthritis in athletes remains asymptomatic initially and it manifested after 15 to 20 years after the start of pathogenesis due to some knee injury, especially ACL and menisci injury.